Manajemen Penyelenggaraan Analisis Jabatan Aparatur Sipil Negara Pada Sekretariat Daerah Provinsi Riau - Riyadi Sudiarto; Ranggi Febrian (UIR Press, 2021)
Fundamentally, the implementation of Bureaucratic Reform within government agencies, both central and regional, mandates an objective change of the proportional bureaucratic institutional structure and the improvement of thequality of the human resources of the apparatus. The President, through The Ministry of State Apparatus Utilization And Bureaucratic Reform, encourages local governments to create government organizations that have the right function,process and size. One way to achieve this is through job analysis. Management of the implementation of a good job analysis will produce a good quality of job requirements planning. Management of the Implementation of Job Analysis consists of planning, organizing, actuating, controlling (Terry Theory) actions, which are carried out to achieveorganizational goals and use professional employees. From the results of research at the Regional Secretariat of Riau Province that in the planning phase, the preparation of the job analysis is carried out before the organizational structure change activity is determined, so that this jump is less effective and has the potential to repeat the preparation of the jobanalysis again. In the organizing phase, the average placement of employees is not based on educational qualifications and competencies. The name of the position attached to the employee actually brings the employee's exclusive nature and cannot do various work tasks (multi-tasking) for the organization. This has the potential to reduce performance and harm the organization. In terms of actuating, organizational leaders are still weak in moving their subordinates to be more professional. In the controlling phase, the preparation of the job analysis is supervised by 2 institutions, namely the Regional Inspectorate and the Supreme Audit Agency. However, in the preparation process, there were several steps thatwere not carried out, such as distributing the questionnaire form or direct interviews, this was not done because the preparation of the job analysis at the Regional Secretariat was already using the application system. Then the Teamwas only formed without a Regional Head Decree. It can be said that it does not have a strong legal umbrella inconducting the preparation of job analysis.